2021
DOI: 10.1039/d0fo03442h
|View full text |Cite
|
Sign up to set email alerts
|

The role of iron homeostasis in adipocyte metabolism

Abstract: Iron plays a vital role in the metabolism of adipose tissue. On the one hand, iron is essential for differentiation, endocrine, energy supply and other physiological functions of adipocyte. Iron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
0
21
0
1
Order By: Relevance
“…This has been shown in visceral adipose tissue. 27 , 28 Aquaporin 7 operates as a glycerol channel in vivo. Adipocyte glycerol permeability has a key role in the regulation of fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown in visceral adipose tissue. 27 , 28 Aquaporin 7 operates as a glycerol channel in vivo. Adipocyte glycerol permeability has a key role in the regulation of fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] By and large, high Hb levels reflect high-level iron stores, which may generate reactive oxygen species (ROS) such as protein carbonyls, AGEs, Ox-LDL and malondialdehyde, 34 which could lead to oxidative stress, consequently resulting β-cell 35 Furthermore, high-level iron stores may cause abnormal uptake or disposal of glucose in liver cells and muscles. [36][37][38][39] Our study has some limitations. First, the pre-pregnancy HB level was obtained from a single spot and screened within 3 months before the last menstrual period, which may not precisely reflect the true pre-pregnancy Hb level.…”
Section: Discussionmentioning
confidence: 94%
“…PLIN2, also known as adipose differentiation-related protein, wraps lipid droplets and phospholipids, as well as participates in the storage of neutral lipids in lipid droplets 46 , 47 . Ma et al showed that the expression of PLIN2 decreased significantly in the iron overload group, iron overload caused ferroptosis in the liver of mice with a decrease in GPX4 expression and an increase in Ptgs2 expression, resulting in a high level of lipid peroxidation, 79% decrease in the protein level of Perilipin-2 (PLIN2) 48 .…”
Section: Discussionmentioning
confidence: 99%